A disc-wind model with correct crossing of all magnetohydrodynamic critical surfaces - Vlahakis, N.; Tsinganos, K.; Sauty, C.; Trussoni, E. (Monthly Notices of the Royal Astronomical Society, 2000)
The classical Blandford & Payne model for the magneto-centrifugal acceleration and collimation of a disc-wind is revisited and refined. In the original model, the gas is cold and the solution is everywhere subfast magnetosonic. In the present model the plasma has a finite temperature and the self-consistent solution of the MHD equations starts with a subslow magnetosonic speed which subsequently crosses all critical points, at the slow magnetosonic, Alfvén and fast magnetosonic separatrix surfaces. The superfast magnetosonic solution thus satisfies MHD causality. Downstream of the fast magnetosonic critical point the poloidal streamlines overfocus towards the axis and the solution is terminated. The validity of the model to disc winds associated with young stellar objects is briefly discussed.
Keywords: Astrophysics; galaxies: jets; ISM: jets and outflows; MHD; PLASMAS; solar wind; stars: mass-loss